Subjective memory complaints and difficulty performing activities of daily living among older women in Australia - Cordier, Reinie; Chen, Y.; Clemson, L.; Byles, J.; Mahoney, N. (Wiley-Blackwell Publishing Asia, 2018)
© 2018 Occupational Therapy Australia Background/aim: Increased age and cognitive decline have been linked to difficulties with activities of daily living (ADL) and instrumental activities of daily living (IADL). Cognitive decline can often be signalled by complaints about one's cognition, such as memory. With older Australians living longer, there is an increasing proportion of the population at risk of declined performance in daily tasks. The aim of this study was to identify if subjective memory complaints in later life among older women predict changes in independence in performing ADL and IADL. Methods: Data were from 3721 women born 1921–1926, who completed Surveys 4–6 of the Australian Longitudinal Study on Women's Health. Memory complaints and difficulties on ADL were measured at each survey, using the Memory Complaint Questionnaire and 16 questions regarding specific ADL. Latent growth modelling examined correlations between initial scores on each measure, changes in measures, and the association between memory complaints and changes in ADL and IADL. Results: There was a significant association between baseline scores for subjective memory difficulty and baseline ADL and IADL scores. Initial memory difficulty was also associated with increase in ADL and IADL difficulty. Conclusions: Subjective memory complaints may be a risk factor for decline in performance on ADL. Attention to these concerns may be important in identifying functional decline in older age.